Access and use of sexual and reproductive health services among resettled refugee and refugee-claimant women in high-income countries: a scoping review protocol. Issue 3 (22nd March 2021) - Stirling Cameron, Emma; Almukhaini, Salma; Dol, Justine; Aston, Megan
ABSTRACT: Objective: The purpose of this review is to understand access to and use of sexual and reproductive health services among resettled refugees and refugee-claimant women in high-income countries. Introduction: Sexual and reproductive health is a critical component of women's well-being and quality of life. Refugee and refugee-claimant women have demonstrated a lower level of sexual health knowledge and reduced usage of sexual and reproductive health services after resettling in high-income countries. This has led to negative outcomes among resettled refugee populations, including unwanted pregnancies and abortion, lower than recommended rates of cervical cancer screening, high rates of sexually transmitted infections, and non-consensual sex. Despite these negative outcomes, no review has been conducted to understand access to and use of sexual and reproductive health services among resettled refugee women in high-income countries. Inclusion criteria: This scoping review will seek to identify studies that describe access to and use of sexual and reproductive health services among refugee and refugee-claimant women who have resettled in a high-income country. Evidence from qualitative, quantitative, mixed method studies, and gray literature will be included. Methods: This review will be conducted in accordance with JBI methodology for scoping reviews. A comprehensive search strategy, developed with a librarian scientist, will be used to identify relevant sources. Titles, abstracts, and full texts will be evaluated against inclusion criteria. Information will be extracted by two independent reviewers using a screening tool. Data will be synthesized and presented narratively, with tables and figures where appropriate.